Cost and appropriateness of treating asthma with fixed-combination drugs in local health care units in Italy - Ruggeri I; Bragato D; Colombo GL; Valla E; Di Matteo S (Dove Medical Press, 2012)
Isabella Ruggeri,1 Donatello Bragato,2 Giorgio L Colombo,3,4 Emanuela Valla,3 Sergio Di Matteo41Servizio Governo Area Farmaceutica, Azienda Sanitaria Locale, Milano, Binasco, 2Data Solution Provider, Milan, 3University of Pavia, Department of Drug Sciences, School of Pharmacy, 4Studi Analisi Valutazioni Economiche, MilanBackground: Bronchial asthma is a chronic airways disease and is considered to be one of the major health problems in the Western world. During the last decade, a significant increase in the use of β2-agonists in combination with inhaled corticosteroids has been observed. The aim of this study was to assess the appropriateness of expenditure on these agents in an asthmatic population treated in a real practice setting.Methods: This study used data for a resident population of 635,906 citizens in the integrated patient database (Banca Dati Assistito) of a local health care unit (Milano 2 Azienda Sanitaria Locale) in the Lombardy region over 3 years (2007–2009). The sample included 3787–4808 patients selected from all citizens aged ≥ 18 years entitled to social security benefits, having a prescription for a corticosteroid + β2-agonist combination, and an ATC code corresponding to R03AK, divided into three groups, ie, pressurized (spray) drugs, inhaled powders, and extrafine formulations. Patients with chronic obstructive lung disease were excluded. Indicators of appropriateness were 1–3 packs per year (underdosed, inappropriate), 4–12 packs per year (presumably appropriate), and ≥13 packs per year (overtreatment, inappropriate).Results: The corticosteroid + β2-agonist combination per treated asthmatic patient increased from 37% in 2007 to 45% in 2009 for the total of prescribed antiasthma drugs, and 28%–32% of patients used the drugs in an appropriate manner (4–12 packs per years). The cost of inappropriately used packs increased combination drug expenditure by about 40%, leading to inefficient use of health care resources. This trend improved during the 3-year observation period. The mean annual cost per patient was higher for powders (€223.95) and sprays (€224.83) than for extrafine formulation (€142.71).Conclusion: Based on this analysis, we suggest implementation of better health care planning and more appropriate prescription practices aimed at optimizing use of health care resources for the treatment of bronchial asthma. The results of our study should be extended to other regional/national reference local health care units, in order to define and compare average standard costs per pathology, and consolidated through the wide sample considered.Keywords: asthma, antiasthma drugs, general medicine, appropriateness, pharmacoeconomics, health economics